References of home buyers in purchasing strata property in Kuantan, Pahang / Nur Amiera Suhana Sahimi - Sahimi, Nur Amiera Suhana (2023)
The increasing demand for high-rise residential buildings and the decline in building values over time have led to a growing interest in the quality of property management services. This research aims to investigate the impact of quality property management on homebuyers' preferences and its effect on the purchasing rate of properties. The study focuses on the district of Kuantan, Pahang, where the occupancy of strata properties has remained relatively low despite their popularity in other capital cities. The problem statement highlights the importance of understanding factors influencing homebuyers' preferences for purchasing strata properties to tackle the high unsold unit rate in the area. The research objectives are to identify and rank the preferences of strata property among homebuyers in Kuantan. To achieve these objectives, a quantitative research method is employed with a questionnaire distributed to potential buyers and current residents of strata properties.